PEMANFAATAN BLOCKCHAIN BAGI AKADEMISI DALAM MENYAMBUT BONUS DEMOGRAFI - Rony Ramadhan Putra (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
Indonesia's population of 250 million is a large market, as smartphone users continue to grow to more than 100 million people. With such a large population, Indonesia will become the country with the fourth largest active smartphone users in the world after China, India and America. However, such a large number does not significantly affect the level of the economy, especially in utilizing blockchain technology that can be applied via smart phones. This study suggests that academics take this opportunity, then educate the young generation of productive age along with the demographic bonus phenomenon.